2022
DOI: 10.1002/ppp3.10327
|View full text |Cite
|
Sign up to set email alerts
|

Herbarium records reveal multiple phases in the relationship between minimum residence time and invasion ranges of alien plant species

Abstract: Societal Impact Statement Plant invasions threaten many native species and change the functioning of ecosystems worldwide. This study finds that the invasion processes of multiple species include lag, acceleration and stable phases. This three‐phase relationship between minimum residence times (the time since the alien species was first recorded) and invasion ranges should be considered when modelling species invasion risks in the future, and we should control the population sizes of these species before they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Pyšek et al., 2003; Rejmánek, 2000), that residence time was positively associated with naturalization. While residence time is frequently correlated with naturalization, one should keep in mind that successfully naturalized species are more likely to be recorded in the wild than non‐naturalized species (Ni, 2023). Indeed, although we found first record data for 620 of the 739 naturalized species (83.9%), we found such data only for 2052 of the 12,979 non‐naturalized species (15.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Pyšek et al., 2003; Rejmánek, 2000), that residence time was positively associated with naturalization. While residence time is frequently correlated with naturalization, one should keep in mind that successfully naturalized species are more likely to be recorded in the wild than non‐naturalized species (Ni, 2023). Indeed, although we found first record data for 620 of the 739 naturalized species (83.9%), we found such data only for 2052 of the 12,979 non‐naturalized species (15.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Invasion processes of non-native plants in novel environments include lag, acceleration, and stable phases [40,41] Previous studies have revealed a significantly linear relationship between the range size of invasive plants and residence time [42,43]. Aikio found that nearly all the New Zealand weed species had a lag-phase, which averaged around 20−30 years, with 4% of species having a lag-phase greater than 40 years [44].…”
Section: Invasive Historical Reconstruction and Key Drivermentioning
confidence: 99%
“… 9 It is also possible that considering the MRT as a covariate for successful naturalization and invasion could have masked or misinterpreted the effects of the biotic and abiotic factors on the MRT. 21 …”
Section: Introductionmentioning
confidence: 99%